Introducing Virtual Reality Technologies to Design Education - Häkkilä, Jonna; Colley, Ashley; Väyrynen, Jani; Yliharju, Antti-Jussi (seminar.net, 2018)
In this paper, we address the introduction of Virtual Reality (VR) tools to the education of industrial design (ID) university students. We present three cases of how we have introduced VR technology in different courses of the industrial design curriculum at the University of Lapland, Finland. As the first example (Case I), we introduced a VR simulation as an empathetic design tool to simulate visual disabilities. The second example (Case II) is reported from a course where students created concepts for a head mounted display (HMD) AR application in smart buildings, and tried out interaction with a HMD VR application. In the third example (Case III), VR was used as a display environment to exhibit students’ 3D industrial design concept models. We report our experiences and lessons learnt, as well as recorded student feedback from the trials. As salient findings, we report the general positive feedback, successful integration with the taught themes especially when connected to physical 3D models, as well as suggested improvements. Hindering the adoption of the technology from the teaching point of view, we report on the lack of infrastructure for multi-user groups in classrooms, the additional effort required to set up the technical system, and limited features supporting multimodality.